"A secret to be burried" : the diary and life of Emily Hawley Gillespie, 1858-1888 - Gillespie, Emily Hawley, 1838-1888 (Bur oak original., 1989)
The sound of nineteenth-century women, once thought lost to us, is alive because ordinary women like Emily Hawley Gillespie gave voice to their thoughts in diaries. This condensed version of the 2,500-page journals of Emily Gillespie, faithfully written from 1858 to 1888, is a detailed account of rural Iowa life. More than this, it contains the reflections of a woman who dreamed of being a painter and writer and instead became a wife and a mother, a woman whose radical convictions were recorded in her diary, while publicly she conformed to the prescribed life of a Victorian pioneer wom.